The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fenrg.2023.1071291
|View full text |Cite
|
Sign up to set email alerts
|

AI explainability and governance in smart energy systems: A review

Abstract: Traditional electrical power grids have long suffered from operational unreliability, instability, inflexibility, and inefficiency. Smart grids (or smart energy systems) continue to transform the energy sector with emerging technologies, renewable energy sources, and other trends. Artificial intelligence (AI) is being applied to smart energy systems to process massive and complex data in this sector and make smart and timely decisions. However, the lack of explainability and governability of AI is a major conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 148 publications
(161 reference statements)
0
9
0
1
Order By: Relevance
“…This paper is part of our broader work on the use of information and communication technology (ICT) to address challenges facing smart cities and societies. Our work on this topic has included the concept of Deep Journalism, 145 , 146 as well as research on topics such as transportation, 146 tourism, 147 smart families and homes, 148 healthcare services for cancer, 58 mental health, 149 education during the COVID-19 pandemic, 150 energy systems 151 and AI-based event detection. 152 Future work will be directed to improving the methodological approach presented in this paper using advanced deep learning methods and their applications to investigate and improve labour economics and other problems facing our societies.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of our broader work on the use of information and communication technology (ICT) to address challenges facing smart cities and societies. Our work on this topic has included the concept of Deep Journalism, 145 , 146 as well as research on topics such as transportation, 146 tourism, 147 smart families and homes, 148 healthcare services for cancer, 58 mental health, 149 education during the COVID-19 pandemic, 150 energy systems 151 and AI-based event detection. 152 Future work will be directed to improving the methodological approach presented in this paper using advanced deep learning methods and their applications to investigate and improve labour economics and other problems facing our societies.…”
Section: Discussionmentioning
confidence: 99%
“…Residential customers as the main users of electrical energy, have a strong influence on electricity demand due to the randomness of their household activities and the flexibility of their appliance usage patterns (Wang et al, 2022). The promotion and application of smart control systems based on energy monitoring, management, and data analysis play a crucial role in optimizing energy utilization and providing personalized recommendations (Alsaigh et al, 2023;Paneru and Tarigan, 2023). The development and diffusion of smart home devices such as smart thermostats, smart lighting and smart appliances support the monitoring and management of energy behavior in the household (Alhussein et al, 2020;Moadab et al, 2021), to better control energy use and improve energy efficiency.…”
Section: Transitioning Towards Smart Energymentioning
confidence: 99%
“…Cocchi et al (2018) demonstrated that machine learning methods have higher prediction accuracy than statistical methods in complex power generation prediction problems. Statistical methods have good interpretability, but machine learning methods are often considered to be "black box problems" (Kane et al, 2014;Alsaigh et al, 2023).…”
Section: Comparisonmentioning
confidence: 99%